Father John Duignam and the Filipino Community of Kalk Bay: Two ministerial partners - Brink, GW (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
For fifty-two years the two partners, Fr. John Duignam and the Filipino community of Kalk Bay, ministered to each other. Their church, St. James Roman Catholic Church (RCC) had been founded in 1858 because of the presence of the Filipino community.